Possible Role of GnIH as a Mediator between Adiposity and Impaired Testicular Function - Anjum, Shabana; Krishna, Amitabh; Tsutsui, Kazuyoshi (Frontiers in Endocrinology, 2016)
The aim of the present study was to evaluate the roles of gonadotropin-inhibitory hormone (GnIH), as an endocrine link between increasing adiposity and impaired testicular function in mice. To achieve this, the effect of GnIH on changes in nutrients uptake and hormonal synthesis/action in the adipose tissue and testis was investigated simultaneously by in vivo study and separately by in vitro study. Mice were treated in vivo with different doses of GnIH for 8 days. In the in vitro study, adipose tissue and testes of mice were cultured with different doses of GnIH with or without insulin or LH for 24 h at 370C. The GnIH treatment in vivo showed increased food intake, up-regulation of glucose transporter 4 (GLUT4) and increased uptake of triglycerides in the adipose tissue. These changes may be responsible for increased accumulation of fat into white adipose tissue, resulted in increase in the body mass. On the contrary to the adipose tissue, treatment with GnIH both in vivo and in vitro showed decreased uptake of glucose by down-regulation of glucose transporter 8 (GLUT8) expressions in the testes, which in turn resulted in the decreased synthesis of testosterone. The GnIH treatment in vivo also showed the decreased expression of insulin receptor protein in the testis which may also be responsible for the decreased testicular activity in the mice. These findings thus suggest that GnIH increases the uptake of glucose and triglycerides in the adipose tissue resulting in increased accumulation of fat, whereas simultaneously in the testis GnIH suppressed the GLUT8 mediated glucose uptake, which in turn may be responsible for decreased testosterone synthesis. This study thus demonstrates GnIH as mediator of increasing adiposity and impaired testicular function in mice.